1997
DOI: 10.1002/hep.510260213
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in oxygen transport in rat liver sinusoids during endotoxemia

Abstract: tor, tumor necrosis factor, and other cytokines. 4 All of these To evaluate the role of nitric oxide (NO) in hepatic micromediators may be involved in the pathogenesis of liver injury, circulation and liver injury during endotoxemia, we studied probably initiated by microvascular disturbance caused by O 2 transport in the hepatic microcirculation of endotoxinleukocyte adhesion to endothelial cells in the hepatic sinuinfused rats. Rats were continuously infused with Escherichia soids. [5][6][7] Nitric oxide (NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In the current study, the dose of l ‐NAME (20 mg kg −1 day −1 ) was sufficient to cause very substantial inhibition of NOS in rats with fulminant hepatic failure and the outcome may be related to the degree of NO inhibition. However, previous reports demonstrated that even much lower doses of l ‐NAME (0·5–5 mg kg −1 ) can induce hepatic microcirculatory dysfunction during endotoxaemia [46,47] and the degree of NOS inhibition did not alter the outcome following infection [48]. Whether lower doses of NOS inhibition by L‐NAME may produce different effects awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the dose of l ‐NAME (20 mg kg −1 day −1 ) was sufficient to cause very substantial inhibition of NOS in rats with fulminant hepatic failure and the outcome may be related to the degree of NO inhibition. However, previous reports demonstrated that even much lower doses of l ‐NAME (0·5–5 mg kg −1 ) can induce hepatic microcirculatory dysfunction during endotoxaemia [46,47] and the degree of NOS inhibition did not alter the outcome following infection [48]. Whether lower doses of NOS inhibition by L‐NAME may produce different effects awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The index of blood volume in regional hepatic tissue [IHB] and the index of blood oxygenation in regional hepatic tissue [ISO 2 ] were monitored using a reflectance spectrophotometry system (TS-200, Sumitomo Electric, Osaka, Japan) before, during, and after hydrodynamic injection at a constant flow rate of 1.2 ml/sec as previously reported [17].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, nonspecific NOS inhibition (L-NMMA and L-NAME) results in increased hepatic damage, while NO donors ameliorate this damage [8, 47, 48, 65, 73]. Although the results are not exactly clear, inhibition of iNOS has been noted to increase hepatic apoptosis [128] and limit PMN accumulation [52].…”
Section: Redox In Pathologic Hepatocytesmentioning
confidence: 99%